Representation of the lyrical passage with nature images - Fayzullaeva Sayatkhan Uzakbaevna (International Journal Of Literature And Languages, 2025)
This article reveals the methods and peculiarities of conveying experiences about the paysage in the poems of poets M.Jumanazarova and P. Mirzabayeva. The lyrical hero in the poems of the poets demonstrates the artist's skill in a unique style through the descriptions of the paysage. In the works of the poets, experiences are artistically expressed on the basis of various details.